Student Labour and Major Research Projects. Issue 1 (16th April 2021) - Mukamal, Anna; Moffatt, Kate; Sharren, Kandice; Battershill, Claire
This essay cluster addresses major Digital Humanities projects from the perspective of the graduate-student research assistants that work on them, focusing on practical and ethical questions about how DH relies on student labour. Cumulatively, this cluster asks how DH projects with feminist aims might integrate those aims into their own practices. Anna Mukamal's essay reflects on and theorizes how her role as Project Manager has provided opportunities for mentorship and collaboration outside of the traditional structures of academic supervision. In Mukamal's experience, the intergenerational and inter-institutional collaboration the Modernist Archives Publishing Project (MAPP) requires has allowed her to foster connections and knowledge that supplement and are adjacent to her graduate coursework and research. Kate Moffatt and Kandice Sharren use their experiences recovering women's largely invisible labour in the eighteenth-century book trades for the Women's Print History Project as a framework to consider what kind of labour might be rendered invisible by large-scale DH work. Their essay focuses on two types of work at risk of being overlooked: the work that goes into confirming an absence of data and the affective labour that goes into developing a team of research assistants. Claire Battershill responds to these essays by offering the perspective of a co-director of a major project that relies on student labour.